Nutritional intake in soccer players of different ages - Ruiz, F.; Irazusta, A.; Gil, S.; Irazusta, J.; Casis, L.; Gil, J. (Journal of Sports Sciences, 2005)
The purpose of this study was to evaluate the dietary practices of soccer players of different ages. The diets of the members of four soccer teams (mean ages of 14.0, 15.0, 16.6 and 20.9 years, respectively) were examined. Our results show that the caloric intake per kilogram of body mass was significantly higher among the youngest players when compared with the adult players (P <0.05). The contribution of carbohydrates to total energy intake was lower than that recommended for athletes. This contribution decreased with age from 47.4% of total energy intake for the 14-year-olds to 44.6% for the adult players. No significant differences in protein or total fat intake were detected among the teams examined. Overall, our results show that the nutritional intake of the soccer players was not optimal, and that this intake was poorer among the adult players than among the adolescents. On the basis of our results, we recommended that nutritional education should be given to soccer players at an early age and should continue throughout adolescence, not only with a view to improving performance but also to promoting more healthy dietary practices in the long term.